Fibre amplifier based on an ytterbium-doped active tapered fibre for the generation of megawatt peak power ultrashort optical pulses. (31st May 2015) - Koptev, M Yu; Anashkina, E A; Bobkov, K K; Likhachev, M E; Levchenko, A E; Aleshkina, S S; Semjonov, S L; Denisov, A N; Bubnov, M M; Lipatov, D S; Laptev, A Yu; Gur'yanov, A N; et al.
Abstract We report a new ytterbium-doped active tapered fibre used in the output amplifier stage of a fibre laser system for the generation of megawatt peak power ultrashort pulses in the microjoule energy range. The tapered fibre is single-mode at its input end (core and cladding diameters of 10 and 80 μm) and multimode at its output end (diameters of 45 and 430 μm), but ultrashort pulses are amplified in a quasi-single-mode regime. Using a hybrid Er/Yb fibre system comprising an erbium master oscillator and amplifier at a wavelength near 1.5 μm, a nonlinear wavelength converter to the 1 μm range and a three-stage ytterbium-doped fibre amplifier, we obtained pulses of 1 μJ energy and 7 ps duration, which were then compressed by a grating-pair dispersion compressor with 60% efficiency to a 130 fs duration, approaching the transform-limited pulse duration. The present experimental data agree well with numerical simulation results for pulse amplification in the threestage amplifier.